Pengembangan Model Pembelajaran Self-Regulated Learning melalui Aktivitas Portofolio berbasis HOTS di Perguruan Tinggi - Herianto, Edy; Rispawati, Rispawati; Alqadri, Bagdawansyah; Fauzan, Ahmad (Universitas Mataram, 2024)
This study aims to address problems in PPKn learning, particularly the low independence of student learning. Previous research has been limited and has not succeeded in achieving quality learning that integrates self-regulated learning (SRL), portfolios, and high-order thinking skills (HOTS), even though PPKn should encompass cognitive, affective, and psychomotor domains in an integrated manner. This study develops a portfolio-based SRL learning model supported by HOTS, along with syntax and guidelines applicable in PPKn study programs and schools. The method employed is research and development (R&D) to produce and validate products during the one semester. The stages include planning, development, testing, revision, and dissemination. The results indicate that, first, the design of SRL-based learning development and portfolios integrated with HOTS has enabled students to engage in critical thinking, problem-solving, and self-reflection in line with the needs of the PPKn study program. Second, the products generated include learning guides for lecturers and students, portfolios of lecture assignments, and evaluation instruments to assess the effectiveness of learning models based on high-order thinking skills